Wyeomyia shannoni Lane & Cerqueira, 1942, a taxonomic puzzle (Diptera: Culicidae): synonymy, genus transfer, homonymy, and description of a new species of Sabethes Robineau-Desvoidy, 1827 - Nascimento-Pereira, Agostinho C.; Neves, Maycon Sebastião Alberto Santos; Guimarães, Anthony Érico; Motta, Monique De Albuquerque; Lourenço-De-Oliveira, Ricardo (Zootaxa, 2021)
We discovered the immature stages of Wyeomyia shannoni Lane & Cerqueira, 1942, unknown for almost 80 years, and found that they, as well as the adult male, are identical with those previously described for Sabethes (Peytonulus) paradoxus Harbach, 2002. Consequently, the species described by Lane and Cerqueira is here considered a senior synonym of Sa. paradoxus and is transferred to the genus Sabethes, hereafter named Sabethes (Peytonulus) shannoni (Lane & Cerqueira, 1942), comb. n. As the name shannoni is preoccupied in the genus Sabethes, the species known as Sabethes (Sabethes) shannoni Cerqueira, 1961 is here renamed Sabethes (Sabethes) cerqueirai Nascimento-Pereira, Neves, Lourenço-de-Oliveira & Motta, nom. n. We improved the morphological characterization of Sa. (Pey.) shannoni (Lane & Cerqueira) by including an illustration of the female genitalia, larval mouthparts and the female genital lobe of the pupa. Finally, we describe and illustrate a new species of Sabethes closely related to Sa. (Pey.) shannoni, named Sabethes (Peytonulus) harbachi Nascimento-Pereira, Guimarães, Lourenço-de-Oliveira & Motta, sp. n.